Orchestrating inflammation: non-coding RNAs as master regulators of macrophage function in chronic obstructive pulmonary disease-an update - Yong, Xinyu; Luo, Xian; Chen, Xiaobing; Yu, Chengxiu (Frontiers in Immunology, 2025)
Chronic obstructive pulmonary disease (COPD) represents a major global health burden, characterized by dysregulated macrophage function and persistent inflammation. Non-coding RNAs (ncRNAs), including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs, have emerged as critical orchestrators of macrophage polarization and inflammatory responses in COPD pathogenesis. This comprehensive review synthesizes current evidence demonstrating how ncRNA-macrophage regulatory axes drive disease progression. Pro-inflammatory miRNAs promote pathological M1 polarization through NF-κB and STAT3 pathways, while protective miRNAs facilitate inflammation resolution. LncRNAs exhibit sophisticated regulatory mechanisms through transcriptional scaffolding and competitive endogenous RNA networks. Clinical studies have successfully translated these mechanistic insights, establishing diagnostic biomarkers and therapeutic targets in human COPD patients. Despite significant progress, challenges remain including methodological heterogeneity, limited understanding of integrated regulatory networks, and clinical translation barriers. Future directions emphasize precision medicine approaches through ncRNA-based diagnostics and combination therapeutics. The evidence strongly supports the therapeutic potential of targeting ncRNA-macrophage regulatory axes, offering transformative opportunities for personalized COPD management and improved patient outcomes.